Derotational distal femur osteotomy with medial patellofemoral ligament reconstruction can get good outcomes in the treatment of recurrent patellar dislocation with excessive TT-TG and increased femoral anteversion - Huo, Zhenhui; Hao, Kuo; Fan, Chongyi; Niu, Yingzhen; Bai, Haotian; Bai, Weixia (Frontiers in Surgery, 2024)
Background Surgery is the main treatment for recurrent patellar dislocation (PD). However, due to the complexity of anatomical factors, there is still a lack of consensus on the choice of combined surgical methods. This study aimed to compare the clinical and radiological outcomes of medial patellofemoral ligament reconstruction combined with derotational distal femur osteotomies (MPFLR + DDFO) and combined with tibial tubercle osteotomies (MPFLR + TTO) for recurrent PD with increased femoral anteversion angles (FAA) and excessive tibial tubercle-trochlear groove (TT-TG) distance.In this retrospective analysis, MPFLR + DDFO and MPFLR + TTO patients from 2015 to 2020 were included. Group A (MPFLR+DDFO, n = 42) and B (MPFLR+TTO, n = 46) were formed.Clinical outcomes included physical examinations, functional outcomes (Kujala, Lysholm, International Knee Documentation Committee (IKDC), visual analog scale (VAS) and intermittent and persistent osteoarthritis pain scale (ICOAP), Tegner scores), and complications. The Caton-Deschamps index (CD-I), patellar title angle, patellar congruence angle, patella-trochlear groove distance, TT-TG distance, and FAA were used to assess radiological outcomes.All clinical outcomes improved significantly in both groups, but Group A had significantly